FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN IBU HAMIL DALAM MEMANFAATKAN LAYANAN VOLUNTARY COUNSELING AND TESTING - Sri Melda Br Bangun; BASYARIAH LUBIS; Raisha Octavariny; Surio Retno (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Currently in Indonesia there is an increase in the prevalence of HIV / AIDS in housewives, followed by a high prevalence of HIV in children. This study used a cross sectional study design with a sample of 50 pregnant women using the stratified random sampling method with the chi-square test. The results showed that there was a relationship between age, work status, knowledge, attitude, and distance of pregnant women in utilizing voluntary counseling and test services